A family segregating lethal neonatal coenzyme Q10 deficiency caused by mutations in COQ9. Issue 4 (20th March 2018) - Smith, Amanda C.; Ito, Yoko; Ahmed, Afsana; Schwartzentruber, Jeremy A.; Beaulieu, Chandree L.; Aberg, Erika; Majewski, Jacek; Bulman, Dennis E.; Horsting‐Wethly, Karina; Koning, Diana Vermunt‐de; Rodenburg, Richard J.; et al.
Abstract: Primary CoQ10 deficiency is a clinically and genetically heterogeneous, autosomal recessive disorder resulting from mutations in genes involved in the synthesis of coenzyme Q10 (CoQ10 ). To date, mutations in nine proteins required for the biosynthesis of CoQ10 cause CoQ10 deficiency with varying clinical presentations. In 2009 the first patient with mutations in COQ9 was reported in an infant with a neonatal‐onset, primary CoQ10 deficiency with multi‐system disease. Here we describe four siblings with a previously undiagnosed lethal disorder characterized by oligohydramnios and intrauterine growth restriction, variable cardiomyopathy, anemia, and renal anomalies. The first and third pregnancy resulted in live born babies with abnormal tone who developed severe, treatment unresponsive lactic acidosis after birth and died hours later. Autopsy on one of the siblings demonstrated brain changes suggestive of the subacute necrotizing encephalopathy of Leigh disease. Whole‐exome sequencing (WES) revealed the siblings shared compound heterozygous mutations in the COQ9 gene with both variants predicted to affect splicing. RT‐PCR on RNA from patient fibroblasts revealed that the c.521 + 2 T > C variant resulted in splicing out of exons 4–5 and the c.711 + 3G > C variant spliced out exon 6, resulting in undetectable levels of COQ9 protein in patient fibroblasts. The biochemical profile of patient fibroblasts demonstrated a drastic reduction in CoQ10 levels. An additional peak on the chromatogram may represent accumulation of demethoxy coenzyme Q (DMQ), which was shown previously to accumulate as a result of a defect in COQ9. This family expands our understanding of this rare metabolic disease and highlights the prenatal onset, clinical variability, severity, and biochemical profile associated with COQ9‐related CoQ10 deficiencies.